Effect of Chelating Agent Concentration on the Pseudocapacitive Performance of V2o5 Flakes Prepared by the Hydrothermal Process for Supercapacitor Applications - Radhalayam, D (SPRINGER, 2025)
Vanadium pentoxide (V2O5) flakes were synthesized via a hydrothermal method by varying the amount of lemon juice (5 mL for sample-1 and 10 mL for sample-2) as a natural chelating agent. Structural and morphological analyses were performed using X-ray diffraction (XRD) and scanning electron microscopy (SEM), confirming crystalline V2O5 with flake-like morphologies influenced by chelating agent concentration. Electrochemical performance was evaluated using cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS) in a 3 M KOH electrolyte. Sample-2 exhibited a Significantly higher Specific capacitance of 1536 F g(-)(1) (CV at 1 mV s(-)(1)) and 212.37 F g(-)(1) (GCD at 1 A g(-)(1)) compared to sample-1, demonstrating that increasing lemon juice concentration enhances the capacitive behavior of V2O5 flakes by improving ion diffusion and electroactive surface area.